2020
DOI: 10.1021/acs.jpcc.0c02143
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative Adsorption of H2O2 on the TiO2(110) Surface for Advanced Oxidation Process

Abstract: Advanced oxidation processes (AOPs) involving the conjugation of H2O2 with metal oxide catalysts such as TiO2 have been studied for a long time because they enable efficient degradation of pollutants in wastewater. The combination of H2O2 and TiO2 is well known to generate oxidizing agents such as •OH and •O2 – radicals by catalytic reactions. However, the reaction mechanism for the production of these radicals is controversial. Here, we investigated the H2O2-dosed surface of rutile TiO2(110) by low-temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…In the second heterogeneous hybrid process, we ran sono-photocatalysis (US/UVTiO 2 ) in the presence of 10 mg L −1 H 2 O 2 and the lowest test dose of the catalyst, (0.1 g L −1 ) and found that while the rate of reaction increased significantly (k = 0.39 min −1 ), the degree of mineralization was reduced from 75.4% without H 2 O 2 to 63.6% with it. The explanation for the rate enhancement is the strong adsorption of H 2 O 2 on the surface of the catalyst [48] . When such a surface is irradiated by UV, the photo-generated electrons react with H 2 O 2 leading to the formation of excess •OH via reductive dissociation [49] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the second heterogeneous hybrid process, we ran sono-photocatalysis (US/UVTiO 2 ) in the presence of 10 mg L −1 H 2 O 2 and the lowest test dose of the catalyst, (0.1 g L −1 ) and found that while the rate of reaction increased significantly (k = 0.39 min −1 ), the degree of mineralization was reduced from 75.4% without H 2 O 2 to 63.6% with it. The explanation for the rate enhancement is the strong adsorption of H 2 O 2 on the surface of the catalyst [48] . When such a surface is irradiated by UV, the photo-generated electrons react with H 2 O 2 leading to the formation of excess •OH via reductive dissociation [49] .…”
Section: Resultsmentioning
confidence: 99%
“…When such a surface is irradiated by UV, the photo-generated electrons react with H 2 O 2 leading to the formation of excess •OH via reductive dissociation [49] . It was also found that molecular H 2 O 2 is attached only on the oxygen vacancies at the surface of TiO 2 forming Ti–O–O–Ti peroxides [48] . Once all peroxides disappear from the surface by reductive dissociation, water molecules adsorb on Ti atoms and remain intact there [49] .…”
Section: Resultsmentioning
confidence: 99%
“…This titanium peroxide further reacts with H 2 O and forms • OH radicals. 44 Figure 6c shows a schematic illustration of the MB dye degradation mechanism on the surface of m-TC40 in the presence of H 2 O 2 . Finally, to see if there was any trace of TiO 2 phase formation in the sample after the first cycle of reaction, we performed additional experiments, and we did not detect any peak related to the TiO 2 phase in XRD analysis (see Figure S10, Supporting Information).…”
Section: Postdegradation Catalyst Stabilitymentioning
confidence: 99%
“…Whereas the BE of Ti 4+ (459.02 eV) in Ti 2p, Ti–O (530.3 eV), and Ti–OH (531.8 eV) in O 1s XPS spectra matches well with the reported value of titanium peroxide (Ti–O–O–Ti). This titanium peroxide further reacts with H 2 O and forms • OH radicals Figure c shows a schematic illustration of the MB dye degradation mechanism on the surface of m-TC40 in the presence of H 2 O 2 .…”
Section: Catalytic Applicationmentioning
confidence: 99%
See 1 more Smart Citation